KAJIAN SEMIOTIKA ROLAND BARTHES DALAM PUISI: SAJAK MATAHARI DAN SAJAK BURUNG-BURUNG KONDOR KARYA W.S RENDRA - Qusayri, Muhammad; Sosrohadi, Somadi; Sukirno, Sukirno (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The representation of the meaning of human value relationships in W.S. Rendra's Sun Rhymes and Condor Birds poems is the main objective of the research. This research is descriptive and qualitative. The data used in the research was sourced from poems by W.S. Rendra that have the titles Sun rhyme and Concert Bird rd Rhyme." The data collection method uses semiotic techniques in reading the text by applying two approaches, namely the heruistic and hermeneutic approaches to reading the text. In analyzing the data, Roland Barthes' semiotic study. The results showed that the relationship between the meaning of poetry and humanity was contained in the five semiotic codes, according to Roland Barthes. In the sun rhyme poem, there are 3 hermeneutic codes, 2 semic codes, 2 symbolic codes, 1 proaeretic code or action code, and 1 referential code or cultural code. In the poem, there are 3 hermeneutic codes, 5 semic codes, 1 symbolic code, and 3 proaeretic codes, or action codes.